Understanding the roles of NiOx in enhancing the photoelectrochemical performance of BiVO4 photoanodes for solar water splitting - Zhang, Mengyuan (2020)
Solar water oxidation is considered as a promising method for efficient utilization of solar energy and bismuth vanadate (BiVO4) is a potential photoanode. Catalyst loading on BiVO4 is often used to tackle the limitations of charge recombination and sluggish kinetics. In this study, amorphous nickel oxide (NiOx) is loaded onto Mo‐doped BiVO4 by photochemical metal–organic deposition method. The resulting NiOx/Mo:BiVO4 photoanodes demonstrate a two‐fold improvement in photocurrent density (2.44 mA cm−2) at 1.23 V versus reversible hydrogen electrode (RHE) compared with the uncatalyzed samples. After NiOx modification the charge‐separation and charge‐transfer efficiencies improve significantly across the entire potential range. It is further elucidated by open‐circuit photovoltage (OCP), time‐resolved‐microwave conductivity (TRMC), and rapid‐scan voltammetry (RSV) measurements that NiOx modification induces larger band bending and promotes efficient charge transfer on the surface of BiVO4. This work provides insight into designing BiVO4‐catalyst assemblies by using a simple surface‐modification route for efficient solar water oxidation.